(untitled) (Bangladesh Journal of Animal Science, 2022)
The purpose of the study was to determine the quality of whey obtained from cow milk using different types of coagulants (microbial rennet, calf rennet, lactic acid and papaya latex). The quality of whey was evaluated with the help of chemical and microbial tests. Results revealed that maximum whey yield (765 mL/L milk) was obtained from lactic acid coagulation which was 17 mL higher than that of the microbial rennet coagulation (p=0.000). The pH was found significantly (p<0.05) higher when the microbial rennet was used as coagulants. Whey obtained by the lactic acid coagulation was superior in terms of chemical quality compared to the whey obtained by coagulating action of other coagulating agents (p=0.000-0.001). Total solids and lactose content was found highest (7.2% and 4.8%, respectively) in lactic acid whey which was significantly higher (≈1%) than that of the other types of whey (p=0.000). In addition, protein content was also found higher (p<0.05) in whey obtained by lactic coagulation. On the other hand, efficiency of fat and ash recovery in curd was found lowest in calf rennet (p=0.000) among the studied coagulants. However, phosphorus content was highest (p=0.005) in calf rennet whey and the whey obtained by microbial rennet coagulation had the lowest (p=0.000) calcium concentration. Microbial load was found maximum (117 cfu × 104/mL) in whey drained out in microbial rennet coagulation, whereas, papaya latex whey had the lowest count (78 cfu × 104/ml), and the microbial count of other two whey was intermediate of them (p=0.000-0.001). In general, considering all the quality attributes, lactic acid whey was found better followed by calf rennet and papaya latex. It indicates more nutrient recovery in the curd produced by the microbial rennet. Bang. J. Anim. Sci. 2021. 50 (2): 107-113